2019
DOI: 10.1080/21691401.2019.1645150
|View full text |Cite|
|
Sign up to set email alerts
|

Baicalein inhibits proliferation and collagen synthesis of mice fibroblast cell line NIH/3T3 by regulation of miR-9/insulin-like growth factor-1 axis

Abstract: The aberrant scar is a challenging problem. Baicalein has effects in attenuating hypertrophic scar formation. Herein, the roles of baicalein in NIH-3T3 were obtained. Cells were treated by baicalein. CCK-8 method and western blot were used to detect cell viability and proliferation-related factors. Furthermore, collagen 1, collagen 3 and a-SMA expression were detected by qRT-PCR and western blot. Besides, total soluble collagen was detected by Sircol assay. In addition, the levels of NF-jB and Wnt/b-catenin si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
(43 reference statements)
0
5
2
Order By: Relevance
“…13 , 78 Comparable to the present study, the pathways involved might include the increment of p53 genes and the decrease of cyclinD1, vascular endothelial growth factor (VEGF), CDK4 genes, and collagen-synthesis-related proteins such as α-smooth muscle actin, collagen-1, and collagen-3 gene expressions. 78 The mechanisms might also happen in the present study, which determined the low toxicity effect of the BRF. The cytoselectivity of an agent towards different cells is an excellent characteristic of a potent anticancer agent.…”
Section: Resultscontrasting
confidence: 43%
See 1 more Smart Citation
“…13 , 78 Comparable to the present study, the pathways involved might include the increment of p53 genes and the decrease of cyclinD1, vascular endothelial growth factor (VEGF), CDK4 genes, and collagen-synthesis-related proteins such as α-smooth muscle actin, collagen-1, and collagen-3 gene expressions. 78 The mechanisms might also happen in the present study, which determined the low toxicity effect of the BRF. The cytoselectivity of an agent towards different cells is an excellent characteristic of a potent anticancer agent.…”
Section: Resultscontrasting
confidence: 43%
“…[75][76][77] BRF or baicalein compound would not disturb the NIH/3T3 cells' proliferation. 13,78 Comparable to the present study, the pathways involved might include the increment of p53 genes and the decrease of cyclinD1, vascular endothelial growth factor (VEGF), CDK4 genes, and collagen-synthesis-related proteins such as α-smooth muscle actin, collagen-1, and collagen-3 gene expressions. 78 The mechanisms might also happen in the present study, which determined the low toxicity effect of the BRF.…”
contrasting
confidence: 43%
“…Sanguisorba minor showed a complex secondary metabolite profile that was influenced by the cut. Flavonoid content increased in leaves obtained from C2, especially the sub-class of flavones, which is characterized by anti-mutagenic, antioxidant, anti-inflammatory, anti-viral and purgative effects and is also highly important in cancer prevention [33][34][35][36][37][38][39]. Moreover, secondary metabolites were downregulated in leaves from C2 as compared to those detected in leaves from C1, as evidenced by the combination of the VIP score (VIP > 1.3) and the fold-change (FC > 2).…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin has also demonstrated other positive features for human health, such as the reduction of plasma levels of low-density lipoproteins and the inhibition of platelet aggregation, thus, its presence in the diet could be very important [33][34][35]. Other studies have shown that baicalein can mitigate cell proliferation and diminish the production of collagen; also, it possesses multiple effective properties for the treatment of different diseases including cancer and injuries [36][37][38][39]. Lastly, 7,4'-dihydroxyflavone, also named 5-deoxyluteolin, has shown impressive antimycobacterial activity and its anti-inflammatory activity is under evaluation [40].…”
Section: Uhplc-qtof Mass Spectrometry Untargeted Profiling and Effectmentioning
confidence: 99%
“…The mechanism of the inhibitory effect of baicalin on HS was related to the TGF-β/Smad2/3 signaling pathways ( Zhang Y. F. et al, 2016 ). Also, baicalin regulates the miR-9/IGF-1 axis to inhibit cell proliferation and collagen production through NF-κB and Wnt/β-catenin signaling pathways ( Yang L. et al, 2019 ).…”
Section: Effects Of Tcm On Hsmentioning
confidence: 99%